Collaborative Writing Strategy for Teaching Writing Descriptive Text: Improving Writing Skills through Collaborative Strategy (Journal of Advances and Scholarly Researches in Allied Education, 2023)
There is a possibility that it will be difficult to find out how to teach developmental writingclasses. Students who have poor writing abilities, limited grasp of what it means to be a writer in anacademic environment, and substantial anxiety about the writing process usually enroll in collegedevelopmental writing courses. Students who are required to spend a semester or more in remedialclasses—which aim to improve skills such as grammar, spelling, and sentence structure—typicallydevelop a pessimistic outlook on education as a result of their experiences. As a result of a lack ofstudent involvement and the stigma that surrounds these courses, students who are enrolled indevelopmental courses may have lower percentages of staying in school, achieving their academicgoals, and graduating. The requirement of negotiation is the second aspect that distinguishescollaboration from other forms of cooperation.